2022
DOI: 10.3390/microorganisms10050841
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomics Revealed the Disturbance of Intestinal Balance in Rabbits with Diarrhea Caused by Stopping the Use of an Antibiotic Diet

Abstract: The harmful effects of diarrhea on the growth performance of rabbits have been well documented, but the details of the potential mechanism of intestinal diarrhea when antibiotics are stopped are still unclear. Here, PacBio sequencing technology was used to sequence the full length 16S rRNA gene of the microbiota of intestinal content samples, in order to characterize the bacterial communities in the small intestine (duodenum and jejunum) and large intestine (colon and cecum) in normal Hyplus rabbits and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Other phyla, such as Verrucomicrobia, Actinobacteria, and Euryarchaeota were found in relatively small abundance but still contributed to shaping the diversity and stability of the microbial community in the rabbit cecum. Although the number of phyla detected in this study was fewer than in the results of a previous study [28], our data confirmed that Bacteroides is a part of the rabbit intestinal microbiota. BSA (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Other phyla, such as Verrucomicrobia, Actinobacteria, and Euryarchaeota were found in relatively small abundance but still contributed to shaping the diversity and stability of the microbial community in the rabbit cecum. Although the number of phyla detected in this study was fewer than in the results of a previous study [28], our data confirmed that Bacteroides is a part of the rabbit intestinal microbiota. BSA (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…This could be attributed to the fact that cecum is the richest and most diverse microbial community in the rabbit gut [14,60]. The significantly different carbohydrates and lipid metabolic activity between the cecum and jejunum we observed could be due to the difference in microbial communities and their capacity to ferment to obtain metabolic energy [9].…”
Section: Discussionmentioning
confidence: 77%
“…The abundance of the Escherichia-Shigella genus in the cecum of NM breed rabbits was positively correlated to body weight gain, as were Enterococcus and both body weight at 12 weeks and body weight gain in the jejunum of the same animals. Escherichia-Shigella should be considered a pathogen in hosts [9]; meanwhile, Enterococcus could be considered a beneficial bacteria that could produce bacteriocins active against bacteria such as Listeria and indigenous clostridia in the gut of rabbits [58]. On the other hand, in the cecum of the GF rabbits, there were significant correlations between Lactobacillus and both the body weight at 12 weeks and the body weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbits have a unique digestive system that relies on a complex interplay of microorganisms in the cecum and colon to digest and absorb nutrients from their food. Disruption of this delicate balance can lead to overgrowth of harmful bacteria, such as Clostridium spp., and can result in diarrhea, enteritis, and even death [ 29 , 41 ]. Antibiotics that are excreted through bile can have a prolonged effect on the gastrointestinal microbiota, leading to dysbiosis even after the antibiotic has been discontinued.…”
mentioning
confidence: 99%